Our Experience of Semi-rigid Ureteroscopy with Pneumatic LithoClast for Impacted Upper Ureteric Calculi - Haider, Ali; Memon, Waqar Ahmed; Yaqoob, Uzair; Zubair, Rabbia; Channa, Muhammad Ali; Mirza, Masoom Raza; Rehman Khan, Muhammad Ahsan (Cerrahpaşa Medical Journal, 2023)
Objective: The aim of this study was to evaluate the outcome of using the semi-rigid ureteroscope and intracorporeal pneumatic lithotripsy on the impacted upper ureteric stones. Methods: This is a retrospective study on patients who underwent ureteroscopy with pneumatic lithoclast fragmentation at Hamdard University Hospital from May 2018 to December 2021. Patients with impacted upper ureteric calculi > 1 cm and having a prior extracorporeal shock wave lithotripsy or medical expulsive therapy of more than 4 weeks were included. Those with persistent pain were also included. Patients <13 years of age, having a distal obstruction, who are pregnant, having spinal deformity, having morbid obesity, or on aspirin were excluded. Results: Out of 72 patients, 53 (73.6%) were males, and the mean age was 39.57 ± 8.81 years. There was a single stone in 66 (91.6%) and multiple in 6 cases. The mean stone diameter was 1.12 ± 0.4 cm. The mean duration of surgery was 32.13 ± 9.71 minutes. The stone-free rate was 79.2% (n = 57), while it migrated in 15 (20.8%) patients which required additional extracorporeal shock wave lithotripsy sessions. A double-J stent insertion was done intraoperatively in 21 (29.1%) patients. No major operative or postoperative complications were observed. Conclusion: Semi-rigid ureteroscope with pneumatic lithotripsy in an experienced hand is still a safe and useful treatment modality for impacted upper ureteric stones with good clearance rates and minimal complications. Cite this article as: Haider A, Ahmed Memon W, Yaqoob U, et al. Our experience of semi-rigid ureteroscopy with pneumatic LithoClast for impacted upper ureteric calculi. Cerrahpaşa Med J. 2023;47(2):168-170.